PEMBELAJARAN INKLUSIF GENDER MELALUI METODE CARD SHORT DI MADRASAH IBTIDAIYAH - Sarifa Suhra (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2017)
This paper discusses Gender inclusive learning through the application of Short card method in Madrasah Ibtidaiyah. Card Short is a collaborative activity that can be used to teach concepts, classifications of properties, facts about an object or review of science that has been given before or repeated information. The dominant physical movement in this method can help be dynamic tired class that can eliminate boredom and enable students to learn together.Gender-inclusive learning in Madrasah Ibtidaiyah implies that in order to involve students in tapping learning materials that have broad sections or categories, the teacher writes the material and its parts into cardboard or others separately. Paper is scrambled and each student is evenly distributed then the teacher gives the card to each student regardless of the social status and gender of the students are all given the opportunity to get involved together in learning